Teaching Topic Preferences in the Nature-Human-Society Subject: How Trainee Teachers Justify Their Likes and Dislikes - Angelika Pahl; Reinhard Tschiesner (MDPI AG, 2024)
This study focuses on the description and explanation of trainee teachers' attitudes in specific educational situations. More precisely, it demonstrates the reasons why they prefer to teach certain Nature-Human-Society topics over others and, conversely, why they do not like teaching some of those topics-particularly science topics relating to physics and technology. The description of these arguments is relevant because trainee teachers' attitudes can have an impact on later teacher behavior, especially in a multidisciplinary subject such as Nature-Human-Society, where different topics can be given different amounts of time and importance in class. The results of this study are based on a survey of a student cohort in teacher training in Switzerland. The arguments for liking or disliking a total of twelve teaching topics in the subject Nature-Human-Society were elicited through open-ended questions and theoretically assigned to three attitude dimensions-cognitive beliefs, affective access, and perceived control-following qualitative content analysis. Differences in the reasons for liking and disliking certain teaching topics are shown, as well as the general finding that liking teaching topics is primarily based on cognitive beliefs, while disliking teaching topics is primarily attributed to lacking perceived control or lacking affective access to trainee teachers.